Pauli Testamentum: 2 Timothy and the last words of Moses - Martin, Seán Charles (Tesi gregoriana, 1997)
The testamentary character of 2 Timothy has long been recognised by its readers. But the allusion to the rebellion of Korah, Dathan, and Abraham (2 Tim 2,19) and the mention of Jannes and Jambres (2 Tim 3,8) introduce into the letter direct references to the figure of Moses. In addition to the biblical narratives, this study examines four other works which include what purport to be Moses' last will and testament: the Vita Mosis of Philo, the Jewish Antiquities of Josephus and the anonymous works Liber Antiquitatum Biblicarum and the Testament of Moses. This study contends that these legends about the last words of Moses constitute the best way to evaluate the portrait of Paul in 2 Timothy, and that Paul is presented in 2 Timothy as a prophet like Moses